Związek psychologii pracy z naukami o zarządzaniu - Wołoszyn, Jan (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2008)
The aim of the essay is to present the relationship between labour psychology and management sciences. In the first part of the article the author presents classical approach to the role of human factor in an enterprise and the views evolution on the human nature. The next part of the essay presents origins of the human relations paradigm and present behaviour view of the enterprise management process. On the basis of conducted analysis the author states that modern management of an organization have to be based on the leadership integrating labour teams around the aim of the organization, taking the advantage of manpower potential with the use of soft methods